Pengaruh Leader Member Exchange (LMX) dan Karakteristik Pekerjaan terhadap Kinerja di Mediasi Kepuasan Kerja (Studi pada Pengadilan Tinggi Jawa Tengah) - Saraswati, Effita Dewi; Tjahjaningsih, Endang (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this research is to examine and analyze the influence of leader-member exchange and job characteristics on job satisfaction. To examine and analyze how job satisfaction mediates the influence of leader-member exchange and job characteristics on employee performance, the population in this study was 76 employees, from staff to leaders, representing all employees of the Central Java High Court. Primary data were collected using questionnaires. Multiple linear regression was used as the data analysis method. The results showed a positive and significant influence of leader-member exchange on job satisfaction, a positive and significant influence of leader-member exchange on employee performance, a positive and significant influence of job characteristics on employee performance, and a positive and significant influence of job satisfaction on employee performance. Job satisfaction mediated the influence of leader-member exchange on employee performance at the Central Java High Court. Therefore, job satisfaction can increase employee potential, with high levels of leader-member exchange improving employee performance. Job satisfaction mediates the influence of job characteristics on employee performance at the Central Java High Court. Therefore, job satisfaction can improve employee performance through job characteristics that align with their field of study.